Industrial economic - Barthwal, R. R. (New Delhi, 1984)
This book presents a general introduction to the subject of Industrial Economics It deals with the study of business policy and decision-making process of the firms and industries. It emphasizes on topics like Market Analysis, Industrial Efficiency, Organizational Goals, Optimum Size of the Firms, Diversifications, Market Concentrations, Profitability Analysis, Financial Analysis, Investment Decisions, Pricing, Growth of the Firm, and Industrial Location etc, etc. The book has a comprehensive coverage of the subject which makes it a unique textbook for the students. Due emphasis has been given in the book on both theoretical discussion and empirical research in the subject. It is useful to the students of economics, commerce business management, and engineering. Research workers in the field of industrial economics would also be benefitted by this book.
Keywords: Industrial organization (Economic theory)